Developing a Skill-Set Model for Industrial Revolution 4.0 (IR4.0) Era: A Conceptual Paper - Khairunnisa, Abdul Aziz; Nurul Ashykin, Abd Aziz; Azim Azuan, Osman; Siti Noorjannah, Abd Halim (Human Resource Management Academic Research Society (HRMARS), 2023)
Most industries are experiencing the Industrial Revolution 4.0 (IR4.0), which requires graduates to learn new skills to be future-proof. Hence, skill preparation for graduates will be crucial. The Malaysia Education Plan 2015-2025 (Higher Education) stated that there is a mismatch in the supply-demand of graduates, with companies claiming that graduates lack the necessary skills and the educational institution not having clear signals of industry's requirement. Previous study indicates the inadequacy in the literature that discussed on the specific IR4.0 skills set needed for business graduates in Malaysia. So, this study aims to (1) explore IR4.0 skills set based on supplies-demand perspective and (2) develop an IR4.0 skills set model for business graduates. Qualitative study will be conducted via Focus Group Discussion (FGD) with service sector and higher education participants. Using NVivo, the model will be developed based on thematic analysis. This study is expected to enhance graduate’s employability. Practically, the study assists the educational institution in building and equip the graduate with the right skills for these IR4.0 era. Furthermore, this study is expected to reduce the skills mismatch.